Cultural Scenario “Martial Quarrel” in Russian Proverbs - V. Van (Научный диалог, 2017)
The experience of the description of the cultural scenario of marital strife as one of the integral components of family life is presented. The material are the proverbs and sayings of the pre-Soviet period. The author relies on linguistic and cultural interpretation of quarrel as an open family conflict, having the verbalization in proverbial fund of Russian national culture - the source of knowledge about the views of the people, in particular on the code of family behaviour. About 300 paremiological units are analyzed. Phases of quarrel as a communicative event depicted in the analyzed linguistic units are identified. Causes of family discord named in the proverbs are fixed. The ways of verbal and nonverbal gender behaviour are named. The views and values of the spouses in a conflict interaction are revealed. The origins of gender conflict are commented. The author argues that male “chauvinism” is manifested in the stereotypical view on the woman, who is vested with such features as stupidity, talkativeness, obstinacy, etc. The idea is stated that harmony and discord as value and anti-value are important in the national family axiosphere, integrate and dezintegrate members of the family miсro-collective.